1984
DOI: 10.1007/bf02409577
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal activity to auditory stimuli in autistic, retarded, and normal children

Abstract: Electrodermal activity to auditory stimuli was compared in 20 autistic children and their matched retarded and normal controls (N = 80). The autistic children were virtually indistinguishable in individual features of electrodermal activity from controls when both chronological and mental age comparisons were accounted for. When patterns of activity were considered globally, both autistic and retarded children could be distinguished from one another and from normal controls. However, in some respects autistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
5

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 27 publications
3
35
0
5
Order By: Relevance
“…In the studies by James (1988, see also James &Barry, 1984), the mean SCR to auditory stimuli was found to be higher in the group of children with autism than in the group of normally developing children. On the other hand, other studies have found no difference in responsiveness to auditory stimuli between children with autism and normally developing children (Palkovitz & Wiesenfeld, 1980;Stevens & Gruzelier, 1984) nor between children with autism and mentally retarded children (Stevens & Gruzelier, 1984). The mental age of the children had no effect on these results.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…In the studies by James (1988, see also James &Barry, 1984), the mean SCR to auditory stimuli was found to be higher in the group of children with autism than in the group of normally developing children. On the other hand, other studies have found no difference in responsiveness to auditory stimuli between children with autism and normally developing children (Palkovitz & Wiesenfeld, 1980;Stevens & Gruzelier, 1984) nor between children with autism and mentally retarded children (Stevens & Gruzelier, 1984). The mental age of the children had no effect on these results.…”
mentioning
confidence: 65%
“…Kyllia¨inen and Hietanen responses to sensory stimuli in children with autism have been mostly studied using auditory stimuli (van Engeland, 1984;Palkovitz & Wiesenfeld, 1980;Stevens & Gruzelier, 1984) and more rarely using both auditory and visual stimuli (Barry & James 1988;van Engeland, Roelofts, Verbaten, & Slangen, 1991;James & Barry, 1984). Studies with auditory stimuli have produced somewhat conflicting results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This failure to make use of extra processing time to rapidly modify response bias is reminiscent of results on slowed shifting of attention in autism (e.g. [236]), and the absence of an effect of prepulse amplitude suggests abnormal sensory responsiveness -a possibility supported by skin conductance findings of abnormally high tonic arousal [216] and abnormally high phasic response to stimuli [241] in autism. Similar findings of high arousal [30] and high responsiveness [156] in FXS support the idea that these abnormal sensory phenomena may be markers of abnormal neural development.…”
Section: Animal Modelsmentioning
confidence: 89%
“…First, cortical EEG abnormalities occur in 40% to 60% of autistic children (Hermelin & O'Connor,1970;Small, 1975;Tsai,Tsai,&August, 1985) but the types of abnormalities vary greatly across children and do not consistently indicate overarousal. Second, when arousal is measured by electrodermal activity (skin conductance level) or heart rate, the findings are contradictory, with some studies suggesting overarousal (Palkovitz & Wiesenfeld, 1980;Sroufe & Waters, 1977) but others, using more controls, failing to find evidence for overarousal (Bernal & Miller, 1971;Stevens & Gruzelier, 1984;van Engeland, 1984). Third, specifically regarding overstimulation, studies of cardiovascular changes (e.g., Kootz & Cohen, 1981) and auditory evoked brainstem responses (e.g., Gillberg, Rosenhall, & Johansson, 1983) indicate inattentiveness to most exteroceptive stimuli and delayed transmission of auditory stimuli in lower functioning autistic children.…”
Section: Alternative Theoriesmentioning
confidence: 99%